(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
The article analyzes the impact of the digital educational environment on the intellectual development of an individual. The use of digital technologies in the modern education system, distance learning, electronic educational resources, and interactive platforms contribute to the effective organization of the learning process. The study highlights the role of the digital educational environment in developing students’ thinking, independent reasoning, creative approach, and information processing skills. In addition, the advantages and certain challenges of an educational environment organized on the basis of digital technologies are also considered.